PENGARUH FASHION LIFESTYLE TERHADAP PURCHASE INTENTION (Studi pada Konsumen Fashion Streetwear Brand H&M di Jabodetabek) - Uke Koesherawati; Kadarisman Hidayat; Rizal Alfisyahr (Fakultas Ilmu Administrasi Universitas Brawijaya, 2019)
The purpose of this research is to know and explain that: (1) Fashion Innovativeness has a partial effect on Purchase Intention. (2) Quality Consciousness has a partial effect on Purchase Intention. (3) Price Consciousness has a partial effect on the Purchase Intention. (4) Brand Consciousness has a partial effect on Purchase Intention. (5) Consumption Status partially significantly affects the Purchase Intention. (6) Fashion Innovativeness, Quality Consciousness, Price Consciousness, Brand Consciousness, Status Consumption simultaneously has significant effect on Purchase Intention. Data analysis In this study is a descriptive analysis and multiple linear regression analyses using SPSS version 25.0 for Windows. The results of this study show that: (1) Fashion Innovativeness has a significant influence on Purchase Intention. (2) Quality Consciousness has a significant effect on Purchase Intention. (3) Price Consciousness has a significant influence on Purchase Intention. (4) Brand Consciousness has a significant effect on Purchase Intention. (5) Consumption Status has a significant influence on Purchase Intention. (6) Fashion Innovativeness, Quality Consciousness, Price Consciousness, Brand Consciousness, Status Consumption has a significant influence on Purchase Intention. Kеywords: Fashion Innovativeness, Quality Consciousness, Price Consciousness, Brand Consciousness, Status Consumption, Purchase Intention АBSTRАK Tujuan penelitian ini adalah untuk mengetahui dan menjelaskan bahwa: (1) Fashion Innovativeness secara parsial berpengaruh signifikan terhadap Purchase Intention. (2) Quality Consciousness secara parsial berpengaruh signifikan terhadap Purchase Intention. (3) Price Consciousness secara parsial berpengaruh signifikan terhadap Purchase Intention. (4) Brand Consciousness secara parsial berpengaruh signifikan terhadap Purchase Intention. (5) Status Consumption secara parsial berpengaruh signifikan terhadap Purchase Intention. (6) Fashion Innovativeness, Quality Consciousness, Price Consciousness, Brand Consciousness, Status Consumption secara simultan berpengaruh signifikan terhadap Purchase Intention. Analisis data dalam penelitian ini yaitu analisis deskriptif dan analisis regresi linear berganda menggunakan SPSS versi 25.0 for Windows. Hasil dari penelitian ini menunjukka bahwa: (1) Fashion Innovativeness memiliki pengaruh signifikan terhadap Purchase Intention. (2) Quality Consciousness memiliki pengaruh signifikan terhadap Purchase Intention. (3) Price Consciousness memiliki pengaruh signifikan terhadap Purchase Intention. (4) Brand Consciousness memiliki pengaruh signifikan terhadap Purchase Intention. (5) Status Consumption memiliki pengaruh signifikan terhadap Purchase Intention. (6) Fashion Innovativeness, Quality Consciousness, Price Consciousness, Brand Consciousness, Status Consumption memiliki pengaruh signifikan terhadap Purchase Intention. Kаtа Kunci: Fashion Innovativeness, Quality Consciousness, Price Consciousness, Brand Consciousness, Status Consumption, Purchase Intention.